2021
DOI: 10.1111/tbed.14066
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the historical lineage I of West Africa against the ongoing spread of the Asian lineage of peste des petits ruminants virus

Abstract: Peste des petits ruminants (PPR) is a highly contagious disease of small ruminants. The causal agent, PPR virus (PPRV), is classified into four genetically distinct lineages. Lineage IV, originally from Asia, has shown a unique capacity to spread across Asia, the Middle East and Africa. Recent studies have reported its presence in two West African countries: Nigeria and Niger. Animals are frequently exchanged between Mali and Niger, which could allow the virus to enter and progress in Mali and to other West Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Furthermore, the circulation of predominantly three PPRV lineages after 2013, following the apparent disappearance of lineage I, since 1989, may have aided the attainment of the maximum effective population. Interestingly, more recent reports, from regions not yet well studied, have demonstrated the ongoing circulation of lineage I in West Africa [4], although full genome analyses have not been available to enable the inclusion of this finding within evolutionary assessments. Future analysis of PPR across West Africa ruminant populations may yield further samples to enable a better evolutionary assessment of lineage I viruses.…”
Section: Evolutionary Rates and Lineage Divergencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the circulation of predominantly three PPRV lineages after 2013, following the apparent disappearance of lineage I, since 1989, may have aided the attainment of the maximum effective population. Interestingly, more recent reports, from regions not yet well studied, have demonstrated the ongoing circulation of lineage I in West Africa [4], although full genome analyses have not been available to enable the inclusion of this finding within evolutionary assessments. Future analysis of PPR across West Africa ruminant populations may yield further samples to enable a better evolutionary assessment of lineage I viruses.…”
Section: Evolutionary Rates and Lineage Divergencementioning
confidence: 99%
“…PPR is caused by the infectious viral agent PPRV, which is a non-segmented negativestrand RNA virus that has been phylogenetically classified, initially by partial sequence analyses and later through full genome analysis, into four distinct genetic lineages (I−IV) [3]. Lineage I contains viruses from West Africa, with very few defined isolates that were believed to have become extinct; however, recent studies have suggested that lineage I PPRV persists in West Africa, despite the emergence of apparently more dominant lineages [4]. Lineage II is also of West African origin, with historic isolates being described from Nigeria and Benin, with more contemporary detections also being from West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…PPRV is classified into four genetically distinct lineages, which can be discriminated based on phylogenetic analysis of short gene regions, often a few hundred nucleotides of the N gene ( Couacy-Hymann et al, 2002 ; Kumar et al, 2014 ). Lineage IV viruses have dominated both the host range and geographic expansion of PPRV seen in recent years and are now replacing other lineages in many African countries ( Libeau, Diallo, and Parida 2014 ; Tounkara et al, 2018 , 2021 ; Dundon, Diallo, and Cattoli 2020 ). Understanding this expansion is critical to mitigate challenges to the PPR GEP and to understand the threat of PPRV to biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Four PPRV lineages (I–IV), all belonging to a single serotype, can be discriminated based on their genetic differences. Lineage I circulation has been historically limited to West Africa; long thought to be extinct, it has recently been detected again in Mali [ 12 ]. Lineage II is present in West and Central Africa, while lineage III has been reported only in East Africa and in the southern part of the Arabian Peninsula [ 13 ].…”
Section: Introductionmentioning
confidence: 99%